Contemplation on Detonation Pressures of Nitramines and Nitro Aromatics. Issue 1 (3rd December 2012) - Türker, Lemi
Abstract A physical model and a mathematical theory for the detonation pressures of explosives materials were developed. The pressure values are expressed as function of the detonation velocity (D) and the average mass (m) of the gaseous products, and are applied for various nitramines and aromatic nitro compounds including nitro pyrimidines and nitro triazines. Some regression equations were obtained and discussed. The pressure values show poor linear dependence on the average mass of the products but good dependence on the detonation velocities alone or Dm. Moreover, for the same Dm value nitramines should produce more pressure than aromatic nitro compounds. This work deals with pressure developed by explosion products and interrelates it with detonation pressure within the constraints of certain assumptions and pays attention to so far unnoticed relationships at least under certain circumstances.